2003
DOI: 10.1021/ac034031z
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Sensors Based on Antibody-Mediated Nanomechanics

Abstract: The use of microfabricated cantilevers as bioaffinity sensors was investigated. Since many bioaffinity interactions involve proteins as receptors, we conducted studies of the magnitude, kinetics, and reversibility of surface stresses caused when common proteins interact with microcantilevers (MCs) with nanostructured (roughened) gold surfaces on one side. Exposure of nanostructured, unfunctionalized MCs to the proteins immunoglobulin G and bovine serum albumin (BSA) resulted in reversible large tensile stresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(72 citation statements)
references
References 30 publications
4
68
0
Order By: Relevance
“…The binding of this particular antigen generated absolute tensile stress of the sensor and reference cantilever, resulting in upward bending of the cantilever spring compared with its original position. Absolute tensile deflections have been also observed previously for physical adsorption of different proteins on a gold surface of a single-cantilever array (34)(35)(36). Note that the generated surface stress is not a result of mass loaded on a cantilever but of the sum of different processes taking place at the cantilever interface, such as protein-surface and proteinprotein interactions whereby the net charge of molecular counterparts plays a key role (35).…”
Section: Resultssupporting
confidence: 69%
“…The binding of this particular antigen generated absolute tensile stress of the sensor and reference cantilever, resulting in upward bending of the cantilever spring compared with its original position. Absolute tensile deflections have been also observed previously for physical adsorption of different proteins on a gold surface of a single-cantilever array (34)(35)(36). Note that the generated surface stress is not a result of mass loaded on a cantilever but of the sum of different processes taking place at the cantilever interface, such as protein-surface and proteinprotein interactions whereby the net charge of molecular counterparts plays a key role (35).…”
Section: Resultssupporting
confidence: 69%
“…The ease of cantilever functionalisation allows for systems as varied as single molecules to whole cells to be studied. In addition, the ability to microfabricate compact arrays of cantilevers facilitates simultaneous and high throughput measurements [128,131].…”
Section: Micro-cantilever Immunosensorsmentioning
confidence: 99%
“…It has been shown that the detection of <0.01% of the L enantiomers in samples of D enantiomers is possible in less than 5 minutes including regeneration of immunoreactor (Silvaieh et al 2002). Anti-D-AA was used in microfabricated cantilevers for enantioselective detection of amino acids based on inducing surface stress by intermolecular forces arising from analyte adsorption on surfaceimmobilized antibodies (Dutta et al 2003). The temporal response of the cantilever allowed the quantitative determination of enantiomeric purity up to an enantiomeric excess of 99.8%.…”
Section: Other Type Of Detectionmentioning
confidence: 99%